The Expression Of Request Strategy Found In Inception Movie: A Pragmatic Study - Krisnoni, Krisnoni, Prof. Endang Fauziati, M.Hum, Prof. Agus Wijayanto, MA., Ph.D (2013)
This research aims to investigate the following questions: (1) to identify the types of request strategies uttered by all the characters in Inception movie (2) to describe the pragmalinguistic forms uttered by all the characters in Inception movie, and (3) to find out the politeness strategy used by the all characters in Inception movie. This research is a descriptive qualitative method. The data of this research are the excerpts of conversation which are produced by all the characters with the other containing request strategy in Inception movie. The collected data are analyzed by determining the type of request strategy in each utterance based on Trosborg's theory. Then, the data are determined its forms of pragmalinguistics based on Kasper's theory. Finally, the degree of politeness is used by all the characters which it is determined using the measurement of politeness strategy based on Brown and Levinson's theory. The last, conclusion is drawn. The results of the study show that, 1) there are four types of request strategies which are used by all the characters in Inception movie. Those are indirect request, conventionally indirect request (hearer-oriented condition), conventionally indirect request (speaker-based condition), and direct request. This is one of four types of request strategies is frequently used. That is direct request found in 48 excerpts in which the obtained request data from Inception movie is 106 excerpts. 2) There are two forms of pragmalinguistics which are applied in internal modification (syntactic downgraders, lexical/phrasal downgraders, and upgraders) and external modification. 3) Furthermore, the result shows all the characters of Inception movie followed the measurement of politeness strategy to determine the types of politeness strategy. The greatest amount of politeness strategy which is used by all the characters is bald-on record that is 72 cases.Based on the description above, the writer gets three conclusions as follows: firstly, in general, direct request is mostly used by all the characters based on request strategy. Secondly, in general, external modification is frequently used by all the characters based on pragmalinguistics forms. Thirdly, in general, bald on-record is frequently used by all the characters based on politeness strategy.